2018
DOI: 10.12659/msm.905833
|View full text |Cite
|
Sign up to set email alerts
|

Triple Negative Breast Cancer Depends on Sphingosine Kinase 1 (SphK1)/Sphingosine-1-Phosphate (S1P)/Sphingosine 1-Phosphate Receptor 3 (S1PR3)/Notch Signaling for Metastasis

Abstract: BackgroundTriple negative breast cancer (TNBC) has a more aggressive recurrence. Previous reports have demonstrated that sphingosine kinase 1 (SphK1) is a crucial regulator of breast cancer progression. However, the correlation of SphK1 with clinical prognosis has been poorly investigated. Thus, we aimed to elaborate the role of SphK1 in TNBC metastasis.Material/MethodsWe first determined the level of SphK1 in breast cancer tissue samples and breast cancer cells. Furthermore, the expression of HER2 and phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 34 publications
2
51
0
Order By: Relevance
“…Cytotoxic effects of doxorubicin and fluorouracil in triple negative breast cancer cells (MDA-MB-231 and its variant LM2-4) were enhanced by silencing of SK1 (97). Functionally, SK1 was shown to regulate the levels of Notch signaling target gene Hes1 via S1P receptor (S1PR) 3-mediated upregulation of Notch intracellular domain (97). Collectively, pharmacological inhibition of SK1 appears to be an effective therapeutic strategy for the treatment of triple negative breast cancer (please see more details in the section SK1 Inhibition as a Therapeutic Tool-Preclinical Evidence).…”
Section: Role Of Sk1 In Breast Cancer Signaling-rationale For Targetimentioning
confidence: 99%
See 3 more Smart Citations
“…Cytotoxic effects of doxorubicin and fluorouracil in triple negative breast cancer cells (MDA-MB-231 and its variant LM2-4) were enhanced by silencing of SK1 (97). Functionally, SK1 was shown to regulate the levels of Notch signaling target gene Hes1 via S1P receptor (S1PR) 3-mediated upregulation of Notch intracellular domain (97). Collectively, pharmacological inhibition of SK1 appears to be an effective therapeutic strategy for the treatment of triple negative breast cancer (please see more details in the section SK1 Inhibition as a Therapeutic Tool-Preclinical Evidence).…”
Section: Role Of Sk1 In Breast Cancer Signaling-rationale For Targetimentioning
confidence: 99%
“…In breast tumors, SK1 mRNA expression was shown to increase through the four stages of breast cancer and was associated with disease progression (93). High levels of SK1 correlated with poorer survival and prognosis in breast cancer patients (97). In patients with invasive ductal carcinoma, high SK1 expression was an independent factor for predicting shorter recurrence-free survival and was significantly associated with more aggressive oncogenic behavior, including higher histological grade, development of distant metastasis, negativity for estrogen, progesterone and HER2 receptors, and triple negativity (91).…”
Section: Patterns and Significance Of Sk1 Expression In Breast Tumorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The promoting functions of SphK1/S1P in TNBC are well defined by compelling evidence. Previous studies reported that SphK1/S1P promoted TNBC metastasis through the Notch signaling pathway [6] and that inhibition of SphK1 reduced TNBC cells growth through the ERK1/2 and AKT pathways [7]. However, the role of SphK2/S1P in these processes is not decisively recognized.…”
Section: Introductionmentioning
confidence: 97%